Parasitological and Molecular Survey of Hepatozoon Infection in Dogs of South-Western Region (Junagadh) of Gujarat, India - Kumar, Binod; Thakre, B. J.; Joseph, Joice P; Brahmbhatt, Nilima N.; Patel, Jeemi A. (International Journal of Livestock Research, 2018)
Hepatozoon infection in 317 dogs of Junagadh region was surveyed by both microscopically and polymerase chain reaction (PCR). Giemsa stained thin blood smear of five dogs (1.58 %) revealed Gamont stage in the white blood cells. Among these five dogs, two were showing severe symptoms like high temperature (106 °F), congested mucous membrane, enlarge lymph node, aggressive behavior and difficulty to put the legs on ground and they died during treatment. Through PCR, 21 dogs (6.62 %) were found positive for Hepatozoon infection, including microscopically positive animals. The 16 dogs, exclusively found positive in PCR test were either symptomless or having mild general health disturbance which were cured by symptomatic treatment. The results indicate the presence of Hepatozoon infection in dog of this region.